If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 5x + -24 Reorder the terms: -4 + 3x = 5x + -24 Reorder the terms: -4 + 3x = -24 + 5x Solving -4 + 3x = -24 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -4 + 3x + -5x = -24 + 5x + -5x Combine like terms: 3x + -5x = -2x -4 + -2x = -24 + 5x + -5x Combine like terms: 5x + -5x = 0 -4 + -2x = -24 + 0 -4 + -2x = -24 Add '4' to each side of the equation. -4 + 4 + -2x = -24 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = -24 + 4 -2x = -24 + 4 Combine like terms: -24 + 4 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 1/3n-6=15 | | 30*365= | | 32x=16x^2 | | tan^2+4tan+2=0 | | 9-4n=7 | | 8m-25=30 | | 3x-4+10x-48=180 | | 3x-(x-(x-3))=-1 | | 3x-4+5x-12=180 | | (252)1/5 | | 8(t-4)+4t=4(3t+5)-10 | | 10(x-1)+4=12x | | 3*x-7=4*4+2 | | 8-2(t+5)=-2t-2 | | 3x/2-(x-1)/3=x/6 | | 6t+26=19t | | 3(y-7)=4(4+2) | | 8-2(t+5)= | | .2(x+3)-.5(x+3)=-.3x-.9 | | (5x-7)=(4x-6) | | 9x-2(2x+3)=x-4 | | -4(-9+x)=8 | | 2x-3(-2x+4)=13+x | | 2lnx=ln(10-3x) | | 3y+-8=y | | 5x^2-25=20x | | -3(6x+7)=-57 | | -5+0.5a=4 | | -3x+25=76 | | 11x-1/4 | | 10x-500=0 | | 2(2)-3y=12 |